Linear growth rate of vyrezub (Rutilus frisii Nordmann, 1840) in the Dnister River basin - V. Gurbyk; A. Mruk; L. Strembitskyi; A. Kucheruk (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To achieve high rates of recruitment of natural localities with vyrezub (Rutilus frisii Nordmann, 1840), it is a priority to increase the size characteristics of fish seeds under aquaculture conditions, which is interdependent on the linear growth rate of different age groups of vyrezub. The results of the study on size characteristics of this species will form the basis of the future technology for its artificial reproduction in Ukraine. Methodology. The incomplete biological analysis was carried out directly at the sampling site, measurements were carried out according to the generally accepted method without removing fish from the water. After measurements, all juveniles were released into their natural habitat alive and unharmed. The age of the fish and scale measurements were determined using an MBS-10 binocular microscope. Based on the results of the measurements, the linear growth of vyrezub by age category was back calculated according to the Lea’s method. The growth rate was assessed using the analysis of growth in absolute and relative values, the specific growth rate of different age groups of the vyrezub. Findings. Results of determining the age structure of the vyrezub population of the Dnister River showed that in the first year of life it is characterized by a length of 55 mm to 120 mm. The results of back calculation of the growth of the vyrezub showed that in the second year of life, most fish have a length of 156 mm, in the third – 273 mm, and in the fourth – about 391 mm. In the future, the linear growth of fish slows down somewhat, which is explained by the period of sexual maturation and the first spawning. In the fifth year of life, the average individual length of the vyrezub was about 445 mm, in the sixth year - 488 mm, in the seventh year of life - 575 mm. At the age-8+, the average individual length of fish body was 640 mm. The results of the reconstruction of growth rate showed that the fastest linear growth rate was observed in the first two years of life. The dynamics of rapid growth was due to the presence of favorable feeding areas for fish juveniles, which allowed them to escape the trophic pressure of predators. In the fourth and fifth years of life, there was a decrease in the linear growth rate, which was explained by the sexual maturation of males and females, as well as the period of the first spawning. Originality. For the first time, the linear structure of vyrezub of the Dnister River and the rivers of its basin within the Ivano-Frankivsk region has been analyzed. The average growth parameters were determined and analyzed, and the linear growth rate of different age groups of the vyrezub was reconstructed. Practical Value. The study results will be the basis for implementing methodological aspects of artificial reproduction of vyrezub to solve the problem of preserving the species diversity of fish species valuable in terms of environmental protection.